SCIENTIFIC-METHODOLOGICAL BASES OF MANAGEMENT OF PRE-COMPETITION TECHNICAL-TACTICAL TRAINING OF HIGHLY QUALIFIED WRESTLERS (Scientific journal of the Fergana State University, 2024)
The purpose of the research is to develop proposals and recommendations for improving the scientific and methodological foundations of pre-competition technical-tactical training of highly qualified wrestlers, improving the compatibility of the training process. Research methods. The article uses theoretical analysis and generalization, modeling, pedagogical observation, pedagogical testing, and mathematical statistical methods. Research results. The scientific-methodological basis of managing the pre-competition technical and tactical training of highly qualified wrestlers was studied and proposals and recommendations were developed to improve the consistency of the training process. To determine the causality of the negative dynamics of the reliability of the Greco-Roman wrestling technique, the features of the competition were studied. Conclusions. Analyzing the number of techniques performed in rack and parter, the general legitimacy of the superiority of parter wrestling was determined. When calculating the data obtained separately for the rack and parter, such a ratio was violated in all the losing fights. In the stand, only 24.4% of all athletes performed effectively. Parterre acceptance was 75.6% and 70.2% respectively. In addition, a ratio of less than 0.48 refers to the characteristics of parterre wrestling.